Conflicts of Interest in Business: A Review of the Concept - Voicu-Dan Dragomir (Journal of Accounting and Management Information Systems (JAMIS), 2017)
All companies admit in their codes of conduct that conflicts of interest (CIs) are a threat to their efficiency, integrity and reputation. Except for insider trading, definitions of CIs are strictly particular to each business and publicly expressed through their codes of ethics. I propose an interpretative analysis of what is understood by conflict of interest in the codes of ethics of the world's ten largest companies, along with a comprehensive review of CIs in several sections: employment, contracting, corporate assets, insider trading and personal investments, competitors, and corporate image. The present paper offers solutions to avoid or resolve CIs in a business context, by combining economic preference with the psychological cognitivist view of self-interest. The conclusion is that a code of ethics and relevant training are protective measures for a company wishing to convince its employees that they are better off not entering CIs.
Keywords: M41; 650; codes of ethics; conflicts of interest; corruption; corporate conduct